Morphological characteristics of heart after induction of therapeutic hypothermia and the introduction of mesenchymal stromal cells in therapy of experimental myocardial infarction. - Trofimova, А. V.; Chizh, N. А.; Belochkina, I. V.; Volina, V. V.; Sandomirskiy, B. P. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Diseases of cardiovascular system still occupy the first place among the causes of death and disability of population. Currently the new methods for stimulating the regeneration of damaged myocardium are actively developing. It is assumed that the transplantation of mesenchymal stromal cells (MSCs) can promote the replacement of necrotic areas by newly formed cardiomyocytes and stimulate angiogenesis in the ischemic area. In the last decade the method of application of therapeutic hypothermia in order to protect heart and brain cells from oxygen starvation in acute coronary and cerebral insufficiency has become widespread. Objective. The purpose of this work was to study the morphological features of necrosis development and cardiac remodeling in myocardial infarction in rats after the induction of therapeutic hypothermia and injection of MSCs. Methods. The experiment was carried out in 60 white outbred male rats. All the animals were divided into 4 groups after modeling of infarction by ligation of a. coronaries sinistra: 1 – control (myocardial infarction), 2 – myocardial infarction and induction of hypothermia for 60 min, 3 – myocardial infarction and once intravenous injection of allogeneic placental MSCs (concentration 1.2×106cells/ml), 4 – myocardial infarction and combined use of hypothermia and injection of MSCs. Heart tissue for morphological studies was taken on 7th, 14th and 30th days of experiment. Morphometric studies of myocardial infarction area was performed using BioVision 4,0 program. The relative area of connective tissue, the vessel relative area and the number of vessels were assessed. Results. In group 4, in contrast to other groups with myocardial infarction, on 7th day of the experiment the reparative processes in myocardium prevailed over destructive ones. Reparation of myocardium was manifested in the stimulation of angiogenesis, the development of collateral circulation and also in the recovery of contractile elements of cardiomyocytes of the peri-infarction zone. The data of morphometric study in group 4 showed the smallest area of connective-tissue scar on the 30th day of the experiment. Conclusion. Transplantation of MSCs, and especially, combination of therapeutic hypothermia and MSC transplantation lead to a significant improvement in vascularization in the infarcted zone and reduces the connective tissue scar square surface.